Instagram Social Media Influence @humas.banjar Towards the Fulfillment of Follower Information - Aprilia Shesarita; Reni Nuraeni (PT Mattawang Mediatama Solution, 2024)
In this era, information technology is developing very rapidly, which makes the communication process easier. The internet, which is specifically for social media, has been used massively as a communication tool, the use of which has even reached government institutions as a form of fulfilling the information needs of the public. The aim of this research is to determine the influence of social media Instagram @humas.banjar as providing information for followers. This research applies a quantitative research methodology by distributing questionnaires. The sampling technique in the research used non-probability, namely purposive sampling with a sample of 100 respondents. The results of the correlation coefficient test found that there was a strong, significant and unidirectional relationship with the calculated t value which had a significant influence of 8.178 > t table 1.660. The conclusion of this research is that there is an influence of the use of social media of 40.6% on fulfilling information needs, the rest is influenced by other factors outside this research. The influence of social media use was 40.6% on fulfilling information needs, the rest was influenced by other factors outside this research.